How do you convert y= 3x^2-5x-y^2 into a polar equation?

1 Answer
Mar 20, 2018

r=-(sintheta+5costheta)/(sin^2theta-3cos^2theta)

Explanation:

For this we need the following:
x=rcostheta
y=rsintheta

rsintheta=3(rcostheta)^2-5(rcostheta)-(rsintheta)^2

rsintheta=3r^2cos^2theta-5rcostheta-r^2sin^2theta

rsintheta+r^2sin^2theta=3r^2cos^2theta-5rcostheta

sintheta+rsin^2theta=3rcos^2theta-5costheta

rsin^2theta-3rcos^2theta=-sintheta-5costheta

r=(-sintheta-5costheta)/(sin^2theta-3cos^2theta)=-(sintheta+5costheta)/(sin^2theta-3cos^2theta)